Unidentified Drug-Related Problems (DRPs) Associated with Self-Medication in Patients with Type 2 Diabetes Mellitus and CKD - Natalia Christine Latjandu; Ida Sa’adah; Patonah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Patients with type 2 diabetes mellitus (T2DM) complicated by chronic kidney disease (CKD) are particularly vulnerable to drug-related problems (DRPs) as a result of altered pharmacokinetics, polypharmacy, and declining renal function. In this population, the practice of self-medication using over-the-counter (OTC) drugs and complementary and alternative medicine (CAM) is common and often not disclosed to healthcare professionals, causing many DRPs to remain undetected in routine clinical care. This systematic review aims to summarize the scientific evidence regarding the prevalence of self-medication among patients with T2DM and CKD and to examine the relationship between self-medication behavior, patient perception, and the occurrence of unidentified DRPs. A comprehensive search of major scientific databases identified twenty-three observational studies published between 2020 and 2025 that met the inclusion criteria. The findings reveal a high prevalence of OTC and CAM use, particularly analgesics, non-steroidal anti-inflammatory drugs, dietary supplements, and herbal products. Frequently reported unidentified DRPs included inappropriate dosing adjustments for renal impairment, potential drug–drug and drug–herb interactions, the use of nephrotoxic agents, and instances of duplicate therapy. Contributing factors to these unidentified DRPs were non-disclosure of self-medication practices, low levels of medication literacy, polypharmacy, and the lack of structured medication review in clinical settings. Overall, self-medication with OTC drugs and CAM represents a significant and underrecognized source of DRPs in patients with T2DM and CKD, emphasizing the need for proactive medication reconciliation processes and pharmacist-led interventions to improve medication safety and patient outcomes.